Exploring the assessment of musical praxis through ICT in the academic context - Escorihuela, Guillem; Cotolí, José Enrique; Botella, Ana María; Porta, Amparo (Frontiers in Education, 2024)
The evaluation of musical praxis involves a nuanced assessment of performer competencies within the intricate dynamics of musical elements, often hindered by subjective influences and the transient nature of performance. This study investigates the integration of Information and Communication Technology (ICT) tools to enhance instrumental praxis evaluation, focusing on French horn applicants to the University of Valencia Philharmonic Orchestra (OFUV). Employing a descriptive observational methodology and utilizing the MAXQDA application for analysis, the study examines key aspects of interpretation through individual recordings. Results demonstrate that ICT applications facilitate transparent and precise evaluation of performance aspects, underscoring the importance of incorporating these tools in performative education. In this regard, 89% of participants found the feedback to be very useful. Leveraging audio-video recordings offers a promising avenue for comprehensive analysis, providing clearer feedback and advocating for their integration by educational authorities and instructors to foster objective evaluation and enhance musical pedagogy.